(untitled) (Global Journal of Science Frontier Research, 2018)
Biodiesel from non-edible oil emerges as one of the most energy-efficient and environmentally friendly options in recent times to fulfill the sustainable future energy needs. Hence, there is a need to produce biodiesel on an industrial scale. In designing a reactor, for a large scale production, the thermodynamic, kinetics and optimization parameters must be studied. In this study, the kinetics of biodiesel production from refined castor seed oil using refluxed calcined snail shell as a catalyst is investigated. The transesterification variables and the level used in kinetics study are obtained from optimization studies carried out as preliminary studies, the experimental conditions of three different runs that gave the highest yield were selected. The kinetics studied of transesterification reaction shows pseudo-first-order kinetics. The rate constants of the reactions at three different runs are 0.03048, 0.03207 and 0.03737 with 496.678 J/Mol and 1652.4263 as activation energy and frequency factor. The lower activation energy may be due to the catalytic activity of refluxed calcined snail shell.